2020
DOI: 10.1186/s13071-020-3894-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Trypanosoma evansi in livestock in Palestine

Abstract: Background: Trypanosoma evansi is the causative agent of surra, a disease that occurs in many animal species. The disease is responsible for substantial losses in global production and can be fatal if not diagnosed early. This study aims to determine the prevalence of T. evansi in livestock, equids and dromedary camels in Palestine. Methods: Blood samples were collected during 2015-2017 from domesticated animals (n = 259 animals; 77% females and 23% males) including camels (n = 87), horses (n = 46), donkeys (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 48 publications
0
17
1
1
Order By: Relevance
“…Theileriosis, anaplasmosis, hemoplasmosis and trypanosomosis are economically important vectorborne diseases of cattle, usually characterized by high morbidity and high mortality in clinical cases [1][2][3][4]. These diseases are ranked among the most common causes of economic losses in livestock industry [2].…”
Section: Introductionmentioning
confidence: 99%
“…Theileriosis, anaplasmosis, hemoplasmosis and trypanosomosis are economically important vectorborne diseases of cattle, usually characterized by high morbidity and high mortality in clinical cases [1][2][3][4]. These diseases are ranked among the most common causes of economic losses in livestock industry [2].…”
Section: Introductionmentioning
confidence: 99%
“…An experimental study in mice showed that real-time PCR is twice as sensitive for the detection of T. evansi than conventional parasitological techniques (Sharma et al, 2012). The most widely used molecular markers for the detection of this parasite are fragments of the ITS-1 (Eberhardt et al, 2014;Njiru et al, 2005;Sharma et al, 2012), variant surface glycoprotein (VSG) (Konnai et al, 2009) and 18S rRNA genes (Ereqat et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Wild mammals, such as puma and feral pigs, can also be infected with T. evansi [ 5 , 6 ]. T. evansi caused diseases are widely distributed in South America, Asia, Africa, and other regions, causing significant economic losses [ 7 ]. Since 2005, several cases of human infection by T. evansi have been reported [ 8–10 ], suggesting the potential of this parasite to be considered as zoonotic [ 11 ].…”
Section: Introductionmentioning
confidence: 99%